Mechanical properties of carbon nanotube/epoxy composites - Gunalan Kesavan. (2011)
Carbon nanotubes have been the subject of much research in the recent years due to their extraordinary combination of robust mechanical properties, unique structure-dependent electrical conductivity and superior thermal conduction. This project aims to investigate the mechanical properties of single-walled carbon nanotubes bundles produced by the arc-discharge method. This is done by embedding the said carbon nanotubes into an epoxy matrix, forming a composite of 0.9 to 1.9% volume fraction and 0.9 to 1.8 wt %. These composites were then put through compression test using a microtester. The resulting fracture surface was studied using scanning electron microscopy. From the testing, it was found that the carbon nanotubes/epoxy composite has higher strength and stiffness as compared to pure epoxy. When compared to carbon fiber/epoxy composites however, the carbon nanotubes/epoxy composites actually were of lower strength. Carbon nanotubes as a filler agent for composites is a promising potential application for advanced materials as it does offer enhanced mechanical properties in addition to electrical conductivity and high thermal conductivity.